The Effect of Hydrogen Enrichment on The Exhaust Emission Characteristic in A Spark Ignition Engine Fueled by Gasoline-Bioethanol Blends - Rahman, Abdul; Asnawi, Asnawi; Putra, Reza; Radian, Hagi; Waluyo, Tri (Malikussaleh University, Aceh, Indonesia, 2022)
Bioethanol characteristics can be used as an alternative fuel to spark-ignition (SI) engines to reduce emissions. This experiment evaluates the production of emissions for SI engines using hydrogen enrichment in the gasoline-bioethanol fuel blends. The fraction of bioethanol fuel blend was added to the gasoline fuel of 10% by volume and hydrogen fuel produced by the electrolysis process with a dry cell electrolyzer. The NaOH was used as an electrolyte which is dissolved in water of 5% by a mass fraction. The test is conducted using a single-cylinder 155cc gasoline engine with sensors and an interface connected to a computer to control loading and record all sensor variables in real-time. Hydrogen produced from the electrolysis reactor is injected through the intake manifold using two injectors, hydrogen injected simultaneously at a specific time with a gasoline-bioethanol fuel. The test was conducted with variations of engine speeds. The emission product of ethanol–H2 (BE10+H2) was an excellent candidate as a new alternative of fuel solution in the future. The engasolinerichment of hydrogen increased the flame speed and generated a stable combustion reaction. The hydrogen enrichment produced CO2 emission due to the unavailability of carbon content in hydrogen fuel. As a result, the C/H ratio is lower than for mixed fuels.